Semantics of genitive objects in russian a study of genitive of negation and intensional genitive case - Kagan, Olga (Studies in natural language and linguistic theory, 2013)
The genitive/accusative opposition in Slavic languages is a decades-old linguistic conundrum. Shedding new light on this perplexing object-case alternation in Russian, this volume analyzes two variants of genitive objects that alternate with accusative complements—the genitive of negation and the intensional genitive. The author contends that these variants are manifestations of the same phenomenon, and thus require an integrated analysis. Further, that the choice of case is sensitive to factors that fuse semantics and pragmatics, and that the genitive case is assigned to objects denoting properties at the same time as they lack commitment to existence. Kagan’s subtle analysis accounts for the complex relations between case-marking and other properties, such as definiteness, specificity, number and aspect. It also reveals a correlation between the genitive case and the subjunctive mood, and relates her overarching subject matter to other instances of differential object-marking. 1. Non-canonical genitive: how many cases? -- 2. Previously proposed accounts -- 3. Subjunctive mood and the notion of commitment -- 4. Irrealis genitive: formulating the analysis -- 5. Irrealis genitive and relative existential commitment: part 1 -- 6. Irrealis genitive and relative existential commitment: part 2 -- 7. The interaction of case with aspect and number -- 8. Irrealis genitive in a broader context -- Conclusion.